The Music Therapy Effect on Lowering Blood Pressure In Elderly With Hypertension: A Systematic Review - Winarto, Agnestria; Kusnanto, Kusnanto; Harmayetty, Harmayetty (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Hypertension is a major risk factor for cardiovascular disease, morbidity, and also mortality world wide, especially in the elderly. Music therapy provides many benefits for people with hypertension such as lowering blood pressure, and lowering anxiety, stress, and pain. The study aimed to assess music therapy’s effectiveness to provide beneficial effects for the elderly with hypertension. We systematically searched from six English language databases (Scopus, CINAHL, Science Direct, Google Scholar, Proquest, and PubMed) published from 2011 to 2021. Twelve articles included Randomized control trials (RCTs), quasi-experiment, and case reports were reviewed using PRISMA protocol and methodological quality and result. Seven articles from ten articles showed music therapy’s effectiveness for lowering blood pressure in elderly with hypertension. This review suggests that music therapy could be done as a part of complementary therapy to lower blood pressure